Interweaving Story and Theory - Sona Baldrian (Politikon)
Based on organizational autoethnography, this article provides a personal account of how the women’s movement in Armenia has navigated the influx of democratization aid following the 2018 regime change. It examines how the overflow of development aid has transmuted the relationship between women’s rights NGOs and the Armenian state, leading to the further bureaucratization, professionalization, and institutionalization of the women’s movement. Drawing on the author’s personal experiences within the NGOized movement, the article explores the specific ways in which the political economy of gender aid has facilitated anti-feminist and anti-class struggle agendas, showing how close collaboration with the state and donor organizations has shrunk spaces for feminist organizing, impeding critical knowledge production and public mobilization efforts. It also examines the anti-gender dynamics within the local movement, highlighting how the concept of gender has been stripped of its revolutionary essence and operationalized for grants in essentialist and rather conservative terms. The article concludes by advocating for a critical reassessment of the NGO form, arguing for the need to explore alternative forms of feminist organizing that resist and move beyond the limits posed by NGOization.